The season : a social history of the debutante - Richardson, Kristen (W.W. Norton & Company, 2020)
"The world of debutantes opens into a revealing story of women across six centuries, their limited options, and their desires. Digging into the roots of the debutante ritual, with its ballrooms and white dresses, Kristen Richardson- herself descended from a line of debutantes- was fascinated to discover that the debutante ritual places our contemporary ideas about women and marriage in a new light. In this brilliant history of the phenomenon, Richardson shares debutantes' own words-from diaries, letters, and interviews-throughout her vivid telling, beginning in Henry VIII's era, sweeping through Queen Elizabeth I's court, crossing back and forth the Atlantic to colonial Philadelphia, African American communities, Jane Austen's England, and Mrs. Astor's parties, ultimately arriving at the contemporary New York Infirmary and International balls. Whether maligned for its archaic attitude and objectification of women or praised for raising money for charities and providing a necessary coming- of- age ritual, the debutante tradition has more to tell us in this entertaining and illuminating book"--